2017
DOI: 10.3390/app7070666
|View full text |Cite|
|
Sign up to set email alerts
|

Auditory Distance Control Using a Variable-Directivity Loudspeaker

Abstract: Abstract:The directivity of a sound source in a room influences the D/R ratio and thus the auditory distance. This study proposes various third-order beampattern pattern designs for a precise control of the D/R ratio. A comprehensive experimental study is conducted to investigate the hereby achieved effect on the auditory distance. Our first experiment auralizes the directivity variations using a virtual directional sound source in a virtual room using playback by a 24-channel loudspeaker ring. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Wendt extended Laitinen's work by experiments employing a simulation of a third-order directional source in a virtual room (third-order image source model) played back by a loudspeaker ring in an anechoic room [16]. He could show that the perceived distance between the listener and the higher-order directional source could not only be controlled by the order of the directivity pattern but also by the orientation of the source (towards the listener, away from the listener).…”
Section: Perceived Distancementioning
confidence: 95%
See 1 more Smart Citation
“…Wendt extended Laitinen's work by experiments employing a simulation of a third-order directional source in a virtual room (third-order image source model) played back by a loudspeaker ring in an anechoic room [16]. He could show that the perceived distance between the listener and the higher-order directional source could not only be controlled by the order of the directivity pattern but also by the orientation of the source (towards the listener, away from the listener).…”
Section: Perceived Distancementioning
confidence: 95%
“…The study in [16] showed that distance control by changing the directivity and its orientation can also be achieved with the IKO in a real room, cf. Fig.…”
Section: Static Auditory Objectsmentioning
confidence: 99%
“…Wendt, Zotter, Frank, and Höldrich [7] investigated the way to control the perceived distance through the variation of source directivities. The influence of the auralized room, source-listener distance, signal, and single-channel reverberation are considered together to build a model predicting the perceived distance.…”
Section: Advanced Signal Processing Technologies For Spatial Audiomentioning
confidence: 99%
“…Despite the level thresholds being often only accomplished for a limited set of the available reflection paths, the control of auditory distance succeeds, which, as in Zahorik [20], is based on controlling the direct-to-diffuse energy ratio. Laitinen [21] and Wendt [22] present experiments that use compact spherical beamformer arrays to vary distance impressions by crossfading between direct and indirect, rather diffuse sound reinforcement. In previous studies [23][24][25][26], we were able to show the basic characteristics of static and dynamic beamforming in various experiments using stationary and transient sounds.…”
Section: Introductionmentioning
confidence: 99%